Legal basis of trade of veterinary drugs through the example of “Trifuzol” in the republic of Belarus: prospects and issues - Anishchenko, M. A.; Parchenko, V. V.; Hamburh, I. A.; Hamburh, A. V.; Alekseev, O. H.; Samura, T. O.; Makukh, O. V.; Gutyj, B. V.; Hunchak, V. M.; Kulish, S. M.; Samko, A. V.; Аніщенко, Михайло Анатолійович; et al. (India, 2019)
This article covers the issues of legal regulation of trade of veterinary medicinal products in the Republic of Belarus based on the actual Belarusian law and international legal acts of the Eurasian Economic Union (EAEU); underlines the importance and development prospects for the market of veterinary drugs on EAEU territory through the example of veterinary medicine “Trifuzol” for owners of property and nonproperty rights for the specified drugs imported from other countries; new suggestions regarding the amendments in laws that control trade of veterinary drugs have been developed.
Keywords: circulation of veterinary pharmacy preparations; legislation of the Republic of Belarus; international legal acts of the Eurasian Economic Union